Relationship between Concentration and Discharge on Storm Events: Case Study at Cakardipa Catchment, Cisukabirus Subwatershed, Upper Ciliwung Watershed, Bogor, West Java - Nani Heryani; Hidayat Pawitan; Mohamad Yanuar Jarwadi Purwanto; Kasdi Subagyono (UNIVERSITY OF LAMPUNG, 2012)
River nutrient loadings rates are frequently determined from discharge and hydrochemistry relationships using regression techniques. Unfortunately such methods as a conventional technique are inadequate for dealing with the problem such as differences in shape and direction of loop forming in individual and seasonal storms. Besides the relationships are nonlinear and time-dependent, they also varies from site to site. There is a currently method to study hysteresis between discharge and concentration of hydrochemistry. The relationship between discharge and solute concentration was investigated at Cakardipa catchment, Upper Ciliwung watershed, between the years of 2009-2010. The characteristics of the hysteresis loops were used to evaluate the temporal variation of the relative contribution to stream flow of source waters at Cakardipa Catchment including groundwater (CG), soil water (CSO), and rain water (CR). Chemical water analysis was carried out on 497 water samples on storm event. The chemical analysis of storm event of Februari 14, 2010 was carried out for the concentrations of K+, Ca2+, Mg2+, Na+, SiO2, SO42-NO3-, Cl-, and HCO3-. Results of the experiment showed that concentrations displayed circular hysteresis loops during the events, highlighting the complex relation among solutes and discharge during storm hydrographs. The solutes of K, Na, and Ca produced concave curvature, anti-clockwise hysteresis loops, and positive trend, so that classified as A2 loops with components ranking were CR> CG> CSO. .The solutes of Mg, SO4, NO3 assumed to come from groundwater produced convex curvature, clockwise hysteresis loops, and positive trend, indicating a concentration component ranking of CG > CR > CSO (C2 model). While Si and Cl produced clockwise hysteresis loops, indicating a concentration component ranking of CG> CSO> CR which was C1 model.